How to Sell Handicraft Products Online With the Right Marketing Concept? - Andi Hamzah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
The pandemic has weakened business activities in all sectors, both domestically and globally. The impact of this decline was an economic contraction and high inflation. These conditions exacerbate the situation, which makes economic activities especially in the MSME sector even more difficult. However, the presence of the online market is a new hope for this problem. Where business actors can still sell their products, because the reach of the online market is very wide, even overseas. This is an opportunity that needs to be responded to with digital marketing knowledge and skills. Therefore, community service activities are carried out, as one of the efforts to encourage increased sales of handicraft products in the Aceh region. Participants in this activity consisted of all layers of handicraft business actors, totaling 50 people. The method used in this activity is training and mentoring. In this activity, the participants were provided with theoretical knowledge related to online markets and digital marketing, then were taught directly how to create online stores in various major marketplaces in Indonesia, and were further guided how to create advertisements and place advertisements on social media and Google. During the activity, the participants followed closely and enthusiastically, there were even some business actors who were also given assistance in creating a business entity CV.